KULINER PEMPEK UDANG DI DESA BELO LAUT MENDUKUNG PARIWISATA KOTA MENTOK, KABUPATEN BANGKA BARAT - kurniawan, ardiansyah; Kuniawan, Andri; Setyawan, Ryand Daddy; Sari, Ayu Permata; Triswiyana, Ira; Anjani, Tiara Puspa (Amaliah: Jurnal Pengabdian Kepada Masyarakat, 2024)
The town of Mentok, located in West Bangka Regency, holds unique tourism potential distinct from other regions in the Bangka Belitung Islands Province. The combination of maritime tourism and the historical exile of Indonesia's first president is a key advantage for tourism in this district. Mentok is known for its distinctive seafood-based specialty, shrimp pempek, which sets it apart from other places. Belo Laut Village is the production center of this culinary specialty. Despite the uniqueness and strong association of shrimp pempek with Mentok, there has been no branding or effort to promote this local dish as a tourism asset for the town. The community service was conducted in Belo Laut Village, Mentok District, West Bangka Regency, focusing on the Kemplang Yuk Yen Poklahsar group using a Community-Based Approach and Educational Outreach methods. Shrimp pempek has become a distinctive culinary specialty strongly associated with the town of Mentok. This is similar to other regional dishes like gudeg in Yogyakarta, apple chips in Batu/Malang, and breadfruit chips in Belitung. However, the marketing orientation of shrimp pempek remains local. The product has significant potential for further development in terms of production, food safety, packaging, branding, and promotion to support Mentok's culinary tourism sector.